2017
DOI: 10.12681/bgsg.11158
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Studies and Tectonism of the Hellenides

Abstract: By constraining gravity modelling by Deep Seismic Soundings (DSS) and the Bouguer gravity field of Greece a 3-D density-velocity model of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
19

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 11 publications
1
10
0
19
Order By: Relevance
“…This segment of the western Hellenic margin is seismically very active (Makropoulos and Burton, 1981;Papazachos and Papazachou, 1997) deforming rapidly with many destructive earthquakes, landslides and a tremendous bathymetric depression of approximately 5000 m in the Matapan basin. Isostasy is also disturbed, and as Makris (1977) showed, at the Peloponnese-Ionian Sea transition the isostatic balance is under compensated.…”
Section: Geological Settingmentioning
confidence: 93%
“…This segment of the western Hellenic margin is seismically very active (Makropoulos and Burton, 1981;Papazachos and Papazachou, 1997) deforming rapidly with many destructive earthquakes, landslides and a tremendous bathymetric depression of approximately 5000 m in the Matapan basin. Isostasy is also disturbed, and as Makris (1977) showed, at the Peloponnese-Ionian Sea transition the isostatic balance is under compensated.…”
Section: Geological Settingmentioning
confidence: 93%
“…The Aegean crust south of Crete is covered by sediments having a thickness of 6 to 7 km, and then 10 km of continental crust follows plus 6.5 km of subducted oceanic crust. Below western Crete the 21-25 km continental crust is followed by 6.5 km of oceanic crust resulting in a Moho depth at 30-32 km as previously defined by Makris (1977), Makris and Vees (1977), Tsokas and Hansen (1997), and Bohnhoff et al (2001). Sodoudi (2005) applied the Ρ and S receiver function analysis observed beneath the southern Aegean Basin to conclude a very thin crust, reaching 26 km eastwards, and a thicker crust at the Cyclades region, and to estimate the Moho depth at about 25-30 km.…”
Section: Main Results Of Seismic Surveys On the Crustal Structure Of mentioning
confidence: 89%
“…McKenzie (1972) and LePichon et al (1984) suggested an extension of NAF with two major extensional rifts, this of Sperchios basin and even more so the Corinth basin rift. Makris (1977Makris ( , 1985, based on gravity observations and seismic reflection and refraction profiles, proposed that the shear of the NAF is dissipated into a number of major dislocations and tensional and sheared features across the north Aegean Sea and the Hellenides (see also Makris and Stobbe, 1984;Ginzburg et al, 1986). Brooks and Ferentinos (1980), based on single channel reflection seismic mapping, showed that faulting in the basins has caused significant post orogenic gravitational slumping, and deformed the sea bottom topography.…”
Section: Introductionmentioning
confidence: 99%